Word meanings in oral and written psychiatrist-patient communication - Koudria, Svetlana; Davtian, Elena (Penerbit Universiti Kebangsaan Malaysia, 2019)
The evolving trends in today’s institutional psychiatrist-patient communication give rise to non-transparent research methods and communication failures in psychiatry. We see the source of such problematic practices in fundamental misunderstanding and misuse of a word as a linguistic unit in modern psychiatric research. Our study focuses on the use of polysemantic words in psychiatrist-patient communication. We explore how psychiatrists and patients interact to infer meanings from words and expressions crucial for the outcome of psychiatrist-patient communication in various institutional settings. The study is qualitative and interdisciplinary: it is a semantic analysis supported by evidence from clinical interviews and enhanced by the observations of a psychiatrist. The results are presented in two parts. Part 1 focuses on the word meaning in an oral clinical interview. We analyze examples of mental patients’ utterances from clinical interviews and describe how psychiatrists elicit meanings from their patients’ utterances in a clinical setting. In Part 2 we describe the different ways in which words are used and interpreted by patients and clinicians in written communication mediated by a psychiatric clinical research questionnaire. We conclude this article by interpreting our results with regard to the objectives and values of the clinical discourse, and discussing whether or not the new ways of word usage boost the institutional capacity of mental health care.